Torsional Vibration Analysis Of Large Rotor System Using Finite-Element and MatLab Procedures - Nassar, Ameen Ahmed (Basrah Journal for Engineering Sciences, 2012)
In this paper, the finite-element and the matlab procedures are used for the torsional analysis of large rotor system. A large rotor system of 13 discs are considered for the purpose of analysis. As a result, the finite-element and matlab procedures are good tools for the analysis of vibration analysis and design of large rotors and their results are accurate in comparison with other literatures. The normal elastic curve and T-ω diagram obtained in this study are an effective illustration for the vibration problems in large rotors, and the developed equation for drawing the normalized elastic curve reduce the need for tabulated calculation of this curve and its very essential for vibration analysts and designers.